Gambaran Work Life Integration pada Karyawan Gen Z: Bahasa Indonesia - Angela, Claudia; Limtara, Wilson Wiedardi; Young, Tjenita; Nathania Lie, Marina Grace; Zamralita, Zamralita; Reza, Ismoro (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
The advance of technology has changed the way individuals, especially Generation Z, manage the boundaries between work and personal life. The concept of Work-Life Integration (WLI) is now widely adopted by the tech-savvy Generation Z who tend to combine work and personal life together. This study aims to explore the level of WLI in Generation Z employees, as well as the demographic factors that might predict it. The study used quantitative methods by distributing questionnaires via Google Form to 93 Generation Z participants who have worked for at least one year. The measurement tool used is the Indonesian adaptation of the Work-Life Boundary Enactment Scale. The level of Work-Life Integration (WLI) of Generation Z employees tends to be medium, with a stronger tendency towards Work-to-Life Integration. No significant differences were found in the level of WLI when evaluated by gender, marital status, number of years working, and job level. Thus, this study provides a preliminary picture of WLI trends in Generation Z while emphasizing the importance of developing flexible work strategies according to the characteristics of this generation.